Stereotaxic gamma knife radiosurgery in a patient with cerebral cavernoma and Evans syndrome - Lizarraga Valderrama, Hector Mijail (2023)
Cerebral cavernoma is an infrequently diagnosed vascular malformation. It is defined as a malformation at the level of the microcerebral vasculature that, depending on the location and if there is a possibility of rupture, leads to an emergency that can end in the death of the patient. On this occasion, we report a case of a patient with cerebral cavernoma associated with Evans syndrome. Surgical management of the lesion was decided due to increased intensity of headache and oral intolerance. Given the coexistence of Evans Syndrome and the high rate of morbidity and mortality, surgical management was decided by stereotaxic radiosurgery with a gamma knife. The use of low-margin doses for treatment with gamma knife for use in brain cavernomas produces controlled management for seizure symptoms and better quality of life expectancy.